OPTIMIZING QUR’AN INSTRUCTION THROUGH THE JIBRIL METHOD TO IMPROVE THE QUALITY OF STUDENTS’ RECITATION - Muhammad Zainal; Hafid (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study aims to optimize Qur'anic education through the application of the Jibril method to improve the recitation skills of students at the Nurul Huda Al-Habibi Kebonan Foundation in Krasak, Kedungjajang, Lumajang. This study employs a library study method with a qualitative approach. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the Miles, Huberman, and Saldana model, which includes data condensation, data presentation, and conclusions. The results of the study indicate that the Jibril method is implemented through a process of repeatedly imitating the teacher’s recitation until the students are able to read the Qur’an well, with proper recitation (tartil), and in accordance with the rules of tajwid. Instruction is conducted both individually and in groups according to the students’ abilities, and is supported by daily, monthly, and annual evaluations. The application of the Jibril method has proven effective in improving the fluency, eloquence, and accuracy of students’ Qur’an recitation. Supporting factors include students’ learning experiences, parental support, facilities and infrastructure, and teacher guidance, while inhibiting factors include differences in students’ baseline abilities, lack of learning motivation, and the limited number of educators proficient in the Jibril method. Therefore, it is necessary to establish a routine of regular Qur’an recitation, provide Jibril method guidebooks, and conduct training for educators to improve the quality of Qur’anic education